2019
DOI: 10.21608/jmh.2019.7186.1045
|View full text |Cite
|
Sign up to set email alerts
|

The possible protective role of omega 3 on liver of L thyroxine treated male albino rats. Histological and immunhistochemical study

Abstract: Background: Hyperthyroidism is a condition associated with oxidative damage of liver. Omega-3 fatty acids are effective in various medical conditions due to antioxidant, anti-inflammatory, anti-apoptotic and anti-fibrotic activities. Aim of the work: Here we evaluate the potential effects of omega-3 fatty acids on experimentally induced hyperthyroidism. Materials and methods: Thirty adult male rats were divided equally into 3 groups; Control group (G1) received saline. Hyperthyroid (GII) received L-thyroxine g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…Examination of Mallory's trichrome stained sections revealed that deposition of collagen fibers significantly increased in the connective tissue septa around the pancreatic acini, ducts and blood vessels of the hyperthyroid group. This was in accordance with Meligy et al (24) who examined the liver of hyperthyroid rats and observed significant increase in the collagen deposition and Hegazy et al (25) who found that hyperthyroidism accompanied with marked thickness in the capsule of the testes indicating that the collagen fibers deposition increased in the capsule as well as around the blood vessels. Safadi and Friedman (26) explained the increase of liver fibrosis that it might resulted from activation of stellate cells by ROS and subsequent increase in collagen synthesis and fibrogenesis.…”
Section: Discussionsupporting
confidence: 89%
“…Examination of Mallory's trichrome stained sections revealed that deposition of collagen fibers significantly increased in the connective tissue septa around the pancreatic acini, ducts and blood vessels of the hyperthyroid group. This was in accordance with Meligy et al (24) who examined the liver of hyperthyroid rats and observed significant increase in the collagen deposition and Hegazy et al (25) who found that hyperthyroidism accompanied with marked thickness in the capsule of the testes indicating that the collagen fibers deposition increased in the capsule as well as around the blood vessels. Safadi and Friedman (26) explained the increase of liver fibrosis that it might resulted from activation of stellate cells by ROS and subsequent increase in collagen synthesis and fibrogenesis.…”
Section: Discussionsupporting
confidence: 89%
“…Hyperthyroidism is a condition associated with overproduction and secretion of thyroid hormones. Liver dysfunction has been reported in 37% to 77.9% of patients with hyperthyroidism (13). A well-known negative effect of hyperthyroidism is hepatic toxicity, which is characterized by an increase in serum alanine aminotransferase (ALT) and aspartate aminotransferase (AST) levels (3,13).…”
Section: Discussionmentioning
confidence: 99%
“…Liver dysfunction has been reported in 37% to 77.9% of patients with hyperthyroidism (13). A well-known negative effect of hyperthyroidism is hepatic toxicity, which is characterized by an increase in serum alanine aminotransferase (ALT) and aspartate aminotransferase (AST) levels (3,13). However, the possible mechanism between hyperthyroidism and hepatic dysfunction has not been fully explained (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, a hyperthyroid state is associated with various chronic disorders such as cardiovascular diseases, diabetes and liver diseases [ 39 ], and impaired both the hepatic structure and function [ 4 , 40 ]. Additionally, the prevalence of liver dysfunction in patients with hyperthyroidism has been estimated to be between 37% and 77.9% [ 41 ].…”
Section: Discussionmentioning
confidence: 99%